Aux origines de la polémique anticopernicienne (II) - Lerner, Michel-Pierre (Revue des sciences philosophiques et théologiques, 2006)
In the second half of this study on the origins of the anti-Copernican controversy, the Protestant world’s first reactions to heliocentrism will be looked at. Did Martin Luther really denounce the absurdity of heliocentrism in his famous Table Talk of 1539 ? Without absolutely excluding the possibility that Copernicus may have been Luther’s target, we here put forward a hypothesis, not entirely devoid of probability, on the identity of the person involved, someone whom Luther could quite as well have criticised. We then proceed to evoke the ideas of Andreas Osiander, according to whom Copernicus’ theory could not describe the real structure of the world. Osiander had inserted at the beginning of the De revolutionibus, an anonymous notice to the reader, in which he defended an « instrumentalist » reading of heliocentrism. If doubtless in doing this, he protected Copernicus’ work from the attacks of certain theologians, he also provided the upholders of tradition with an argument against the defenders of heliocentrism. The third part of this paper deals with the reaction of Philipp Melanchthon. In his Initia doctrinae physicae, he criticized heliocentrism as a false cosmological doctrine. But Melanchthon did not totally reject Copernicus. His eschatological interests led him to consider as real the (supposed) diminution of solar excentricity postulated by Copernicus. This Melanchthon interpreted as one of the « signs » sent to men by God to warn them of the coming end of time. In the Initia there is emphatic praise of the observations and of the mathematical part of the new astronomy, held, as it were, to advance the cause of the Reformation. This explains why Melanchthon strongly encouraged Copernican studies, especially in giving his support to the publication of Erasmus Reinhold’s Prutenic Tables. To conclude, a rapid comparison is drawn of the practical consequences of a biblically inspired anti-Copernicanism for philosophers and astronomers working in a Protestant milieu and for those in the Roman Catholic world, up until the 20’s of the xviith century.